A study and applying of IoT technology to build Theft Prevention System for motorbike = Nghiên cứu xu hướng ứng dụng công nghệ internet of thing (IOY) và ứng dụng xây dựng dịch vụ giám sát định vị và chống trộm xe máy – smart motor - Ngô, Vĩnh Quý (2020)
To propose application of IoT in the design of positioning and theft prevention system for Motorbike of Viettel Group